Roots-eye view: using microdialysis and microCT to non-destructively map root nutrient depletion and accumulation zones - Brackin, Richard; Atkinson, Brian S.; Sturrock, Craig J.; Rasmussen, Amanda (Wiley, 2017)
Improvement in fertiliser use efficiency is a key aspect for achieving sustainable agriculture in order to minimise costs, greenhouse gas emissions and pollution from nutrient runoff. To optimise root architecture for nutrient uptake and efficiency we need to understand what the roots encounter in their environment. Traditional methods of nutrient sampling such as salt extractions can only be done at the end of an experiment, are impractical for sampling locations precisely and give total nutrient values which can overestimate the nutrients available to the roots. In contrast, microdialysis provides a non-invasive, continuous method for sampling available nutrients in the soil. Here for the first time we have used microCT imaging to position microdialysis probes at known distances from the roots and then measured the available nitrate and ammonium. We found that nitrate accumulated close to roots while ammonium was depleted demonstrating that this combination of complementary techniques provides a unique ability to measure root-available nutrients non-destructively and in almost real-time.